Pure as the angels, wise as the dead: Perceptions of infants' agency in a Zambian community. (August 2016) - Smørholm, Sesilie
This article is focused on concepts of agency in relation to unborn and newly born babies in a Zambian community. Through an exploration of local perceptions of unborn and newly born babies' spirituality and personhood, as well as their developing bodies, I problematize dominating theoretical definitions of children's agency. The article calls for more relational assessments of children's agencies that not only focus on children as independent social actors in their own right but also integrate experiences of dependency and vulnerability.